Chalcogen Bonding with Diaryl Ditellurides: Evidence from Solid State and Solution Studies. Issue 25 (1st April 2022) - Weiss, Robin; Aubert, Emmanuel; Groslambert, Loic; Pale, Patrick; Mamane, Victor
Abstract: The chalcogen bonding (ChB) ability of Te is studied in symmetrical diaryl ditellurides ArTeTeAr. Among the two Te σ‐holes, the one along the less polarized Te−Te bond was calculated as the more electropositive. This counter‐intuitive situation is due to the hyperconjugation contribution from Te lone pair to the σ* of the adjacent Te which coincides with σ‐hole along the more polarized Te−Ar bond. ArTeTeAr showed notable structural features in the solid state as a result of intermolecular Te⋅⋅⋅Te ChB, such as a Te4 rectangle through dimer aggregation or a triangular Te3 motif, where one Te interacts with both Te atoms of a neighboring molecule through both its σ‐hole and lone pair, in a slightly frustrated geometry. Lewis acidity of ArTeTeAr was also evaluated by NMR with R3 PO as σ‐hole acceptors in different solvents. Thus, 125 Te NMR allowed monitoring Te⋅⋅⋅O interaction and delivering association constants ( K a ) for 1 : 1 adducts. The highest value of K a =90 M −1 was measured for the adduct between ArTeTeAr bearing CF3 groups and Et3 PO in cyclohexane. Notably, by using n Bu3 PO, Te⋅⋅⋅O interaction was revealed by 19 F‐ 1 H HOESY showing spatial proximity between CF3 and CH3 of n Bu3 PO. Abstract : Diaryl ditelluride derivatives bearing different functional groups were prepared with the aim to study their ability to interact through chalcogen bonding (ChB). Rectangular Te4 and triangular Te3 motifs were observed in the solid‐state as a result of intermolecular Te⋅⋅⋅Te ChB. In solution, the use of the very sensitive 125 Te, 17 O NMR analyses as well as 19 F− 1 H HOESY allowed unambiguous detection of a Te⋅⋅⋅O chalcogen bond between the diaryl ditellurides and phosphine oxides.